Thickener for cyanoacrylate adhesives
By using a specific composition methacrylic resin as a thickener, the problems of increased viscosity and poor odor under high temperature and humidity conditions were solved, and better storage stability and use performance were achieved.
Patent Information
- Application Number
- CN202180065913.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-09-13
AI Technical Summary
The existing cyanoacrylate-based adhesives have increased viscosity under high temperature and humidity conditions and have a bad odor, making it difficult to meet the requirements of long-term storage and use stability.
A methacrylic resin containing methyl methacrylate monomer units and an alkyl (meth)acrylate monomer units having 4 or more carbon atoms is used as a thickener. By adjusting the monomer ratio and polymerization conditions, the odor is reduced and the storage stability of the binder is improved.
It effectively reduces the odor of the adhesive, and improves the viscosity stability under high temperature and humidity conditions, extends the storage and service life of the product.
Smart Images

Figure GDA0004145701830000081 
Figure GDA0004145701830000281 
Figure GDA0004145701830000291
Abstract
Description
Technical Field
[0001] The invention relates to a thickener for a cyanoacrylate adhesive and an adhesive. Background Art
[0002] In the manufacture of coatings, adhesives, etc., organic thickeners are used for the purpose of adjusting the viscosity of the product to improve handling properties. Among organic thickeners, thickeners using methacrylic resin compositions have high transmittance and weather resistance as transparent resins, and also have excellent affinity with alkyl cyanoacrylates and other substances and chemical resistance. Since methacrylic resin compositions rapidly dissolve in monomers while maintaining transparency, they are widely used as thickeners for adhesives.
[0003] Among adhesives, cyanoacrylate adhesives are particularly used in a wide range of fields such as industrial, medical, and household use as instant adhesives because of the high anionic polymerizability of the alkyl cyanoacrylate as the main component, which can initiate polymerization with weak anions such as a small amount of water or impurities, and firmly join various materials in a short time.
[0004] Due to its high polymerizability, cyanoacrylate adhesives are transported and stored in an environment that is isolated from the outside air to a certain extent, such as by injecting into a sealed container. However, depending on the conditions of transportation, storage, and use, there are often cases where the adhesive is handled in an environment that may become high temperature and high humidity. If left for a long time under such conditions, the viscosity of the cyanoacrylate adhesive may increase, and therefore improvement is required.
[0005] Furthermore, since cyanoacrylate-based adhesives have not only the odor of cyanoacrylate itself but also the specific odor of the dissolved thickener, it is also necessary to reduce the odor.
[0006] Patent Document 1 discloses an acrylic thickener having excellent solubility in methyl methacrylate having a characteristic molecular weight distribution.
[0007] Patent Document 2 discloses a thickener containing a methacrylic resin having excellent stability when exposed to 50° C. / 95% Rh in methyl methacrylate.
[0008] Patent Document 3 describes that a cyanoacrylate-based adhesive composition contains a polyalkyl (meth)acrylate having a weight average molecular weight of 200,000 to 500,000 as a thickener.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent document 1: Japanese Patent No. 5131956.
[0012] Patent document 2: Japanese Patent Application Publication No. 2018-178076.
[0013] Patent document 3: Japanese Patent Publication No. 4-15267. Summary of the invention
[0014] Problems to be solved by the invention
[0015] As described in Patent Document 1, among acrylic thickeners having a characteristic molecular weight distribution, it is disclosed that the solubility in methyl methacrylate is good, but no consideration is given to the solubility in alkyl cyanoacrylates and the long-term storage / preservation stability when dissolved in alkyl cyanoacrylates that are easily polymerized by a small amount of water or impurities. In addition, no consideration is given to the "odor" when dissolved in alkyl cyanoacrylates, and improvement is required.
[0016] Patent Document 2 provides a thickener having excellent long-term stability in methyl methacrylate by introducing a specific structure into the resin terminal, but does not consider long-term stability in alkyl cyanoacrylate, nor does it consider "odor when dissolved".
[0017] Patent Document 3 describes the use of a relatively high molecular weight acrylic resin as a thickener for a cyanoacrylate adhesive, but does not take odor into consideration.
[0018] Therefore, an object of the present invention is to provide a thickener that can be suitably used as a thickener for adhesives and that can improve odor when used as a thickener for adhesives, particularly for cyanoacrylate-based adhesives.
[0019] Means for solving problems
[0020] The present inventors have conducted intensive studies to solve the above-mentioned problems and have surprisingly found that a less odorous adhesive can be obtained when a methacrylic acid resin containing 95 to 99.9% by mass of methyl methacrylate monomer units and 0.1 to 5% by mass of alkyl (meth)acrylate monomer units having an alkyl group having 4 or more carbon atoms is used, thereby completing the present invention.
[0021] That is, the present invention is as follows.
[0022] [1] A thickener for a cyanoacrylate adhesive, characterized in that the thickener for a cyanoacrylate adhesive comprises a methacrylic resin, wherein the methacrylic resin contains 95 to 99.9% by mass of methyl methacrylate monomer units and 0.1 to 5% by mass of an alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms.
[0023] [2] The thickener for a cyanoacrylate adhesive according to [1], wherein the MMA volatilization amount when 5 mg of the methacrylic resin is heated at 60° C. for 10 minutes is 10 ppm by mass or less.
[0024] [3] The thickener for a cyanoacrylate adhesive according to [1] or [2], wherein the mass ratio of particles having a particle size of 710 μm or more is 5 mass % or less relative to 100 mass % of the thickener for a cyanoacrylate adhesive.
[0025] [4] The thickener for a cyanoacrylate adhesive according to any one of [1] to [3], wherein the pH when the thickener for a cyanoacrylate adhesive is dispersed in water is 2.0 to 9.0.
[0026] [5] The thickener for a cyanoacrylate adhesive according to any one of [1] to [4], wherein the thickener for a cyanoacrylate adhesive has a molecular weight distribution (Mw / Mn) of 2.5 or less.
[0027] [6] An adhesive comprising the thickener for a cyanoacrylate adhesive according to any one of [1] to [5] and an alkyl cyanoacrylate.
[0028] [7] The adhesive according to [6], wherein the viscosity is 0.5 to 10 Pa·s.
[0029] Effects of the Invention
[0030] According to the present invention, a thickener can be provided which can be suitably used as a thickener for adhesives and can improve odor when used as a thickener for adhesives, particularly for cyanoacrylate-based adhesives.
[0031] In addition, the thickener according to an example of the present embodiment can suppress the viscosity increase and solidification of the thickened object during storage, and can improve the storage stability of the product.
[0032] In addition, the thickener according to one example of the present embodiment has excellent stability after dissolution, and has a characteristic that the viscosity is unlikely to increase even when left for a long period of time after dissolution. DETAILED DESCRIPTION
[0033] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail. It should be noted that the present invention is not limited to the following embodiment, and various modifications can be made within the scope of the gist thereof.
[0034] In addition, below, the structural unit which comprises a polymer may be called "-monomeric unit" and / or "-structural unit" containing a some "-monomeric unit".
[0035] In addition, the constituent material of the "-monomer unit" may be simply referred to as "-monomer" by omitting the "unit".
[0036] [Thickener]
[0037] The thickener of the present embodiment includes a methacrylic resin containing at least 95 to 99.9% by mass of methyl methacrylate monomer units and 0.1 to 5% by mass of alkyl (meth)acrylate monomer units having an alkyl group having 4 or more carbon atoms as monomer units.
[0038] The thickener may be composed only of the methacrylic resin.
[0039] The thickener preferably has the methacrylic resin as the resin component alone. The thickener may further contain other methacrylic resins as impurities, but preferably consists of the methacrylic resin alone, and more preferably consists of only one methacrylic resin.
[0040] The thickener is preferably a thickener for cyanoacrylate adhesives.
[0041] The weight average molecular weight of the thickener is preferably 85,000 or more and 1,500,000 or less from the viewpoint of imparting characteristics as a thickener.
[0042] When the weight average molecular weight of the methacrylic resin contained in the thickener is 85,000 or more and less than 300,000, it is preferred that the following formula be satisfied, where the viscosity measured at 25° C. after being dissolved in ethyl cyanoacrylate at a concentration of 20% by mass is denoted as η1, and the viscosity measured at 25° C. after being dissolved in ethyl cyanoacrylate at a concentration of 20% by mass and left to stand at 60° C. for 48 hours is denoted as η2. In this case, the water content of the methacrylic resin measured by a drying method is preferably 0.01% or more and 1% or less.
[0043] 1.0<η2 / η1<5.0
[0044] When the weight average molecular weight of the methacrylic resin contained in the thickener is 300,000 or more and 1,500,000 or less, it is preferred that the following formula be satisfied when the viscosity measured at 25° C. after the methacrylic resin is dissolved in ethyl cyanoacrylate at a concentration of 10% by mass and then left to stand at 60° C. for 48 hours and then dissolved in ethyl cyanoacrylate at a concentration of 10% by mass and then left to stand at 25° C. and then left to stand for 48 hours is expressed as η4. In this case, the water content of the methacrylic resin measured by a drying method is preferably 0.01% or more and 1% or less.
[0045] 1.0<η4 / η3<5.0
[0046] (Methacrylic Resin)
[0047] As the alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms, it is preferred to use a monomer unit derived from an alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms such as n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, and 2-ethylhexyl methacrylate. In particular, the n-butyl acrylate monomer unit is preferred from the viewpoint of easy availability and reduced odor when dissolved in cyanoacrylate.
[0048] The methacrylic resin may consist of only the methyl methacrylate monomer unit and the alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms, or may further contain other monomer units such as other vinyl monomer units copolymerizable with the methyl methacrylate.
[0049] The other monomer units may be vinyl monomers copolymerizable with methyl methacrylate, specifically, alkyl methacrylates having 2 to 3 carbon atoms in the alkyl group; alkyl acrylates having 1 to 3 carbon atoms in the alkyl group; α,β-unsaturated acids such as acrylic acid or methacrylic acid; divalent carboxylic acids containing unsaturated groups such as maleic acid, fumaric acid, and itaconic acid, and their alkyl esters; aromatic vinyl compounds such as styrene, α-methylstyrene, and styrene having substituents on the benzene ring; cyanide vinyl compounds such as acrylonitrile and methacrylonitrile; maleic anhydride, maleimide, N- -substituted maleimide; monomers obtained by esterifying both terminal hydroxyl groups of ethylene glycol or its oligomers with acrylic acid or methacrylate, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; monomers obtained by esterifying two hydroxyl groups of alcohols with acrylic acid or methacrylate, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate; monomers obtained by esterifying polyol derivatives such as trimethylolpropane and pentaerythritol with acrylic acid or methacrylate; multifunctional monomers such as divinylbenzene; etc. These can be used alone or in combination of two or more. From the viewpoint of odor suppression, in the case of containing an alkyl acrylate having an alkyl group with 1 to 3 carbon atoms, the mass ratio of the monomer unit derived from the alkyl acrylate having an alkyl group with 1 to 3 carbon atoms is preferably less than 0.1% by mass, and more preferably not contained, relative to 100% by mass of all monomer units constituting the above-mentioned methacrylic resin.
[0050] The mass ratio of the monomer units derived from methyl methacrylate relative to 100 mass % of the methacrylic resin is 95 to 99.9 mass % from the viewpoint of suppressing odor when dissolved (for example, when dissolved in alkyl cyanoacrylate), more preferably 97.5 to 99.8 mass %, further preferably 99 to 99.8 mass %, and particularly preferably 99.5 to 99.8 mass %.
[0051] The mass ratio of the alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms is 0.1 to 5 mass % relative to 100 mass % of the methacrylic resin. It is more preferably 0.2 to 2.5 mass %, further preferably 0.2 to 1 mass %, and particularly preferably 0.2 to 0.5 mass %. When it exceeds 5 mass %, it is not preferred because when dissolved in alkyl cyanoacrylate, a specific odor is generated due to the remaining alkyl (meth)acrylate monomer having an alkyl group having 4 or more carbon atoms or impurities derived therefrom. When it is less than 0.1 mass %, it is not preferred because the odor improvement effect obtained by copolymerizing the alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms cannot be exerted.
[0052] In the present embodiment, other monomer units may be copolymerized within the range that does not impair the effects of the present application. Considering the solubility in alkyl cyanoacrylates or the odor when dissolved, when the total amount of methyl methacrylate and alkyl (meth)acrylate monomer units having an alkyl group with 4 or more carbon atoms is taken as 100 parts by mass, the mass ratio of monomer units derived from other vinyl monomers copolymerizable with the above methyl methacrylate is preferably 0 to 20 parts by mass, more preferably 15 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less.
[0053] In 100 parts by mass of the methacrylic resin, the total mass ratio of the monomer units derived from methyl methacrylate and the alkyl (meth)acrylate monomer units having an alkyl group having 4 or more carbon atoms is preferably 80 parts by mass or more, more preferably 85 parts by mass or more, further preferably 90 parts by mass or more, further preferably 95 parts by mass or more, and particularly preferably 100 parts by mass.
[0054] The thickener of the present embodiment is a thickener for a cyanoacrylate adhesive. Here, the cyanoacrylate adhesive preferably contains an alkyl cyanoacrylate as a main component (for example, the mass ratio of the alkyl cyanoacrylate is 50 mass % or more, more preferably 70 mass % or more relative to 100 mass % of the adhesive).
[0055] Examples of the alkyl cyanoacrylate include cyanoacrylates having an alkyl group having 1 to 10 carbon atoms, such as methyl cyanoacrylate, ethyl cyanoacrylate, propyl cyanoacrylate, isopropyl cyanoacrylate, butyl cyanoacrylate, isobutyl cyanoacrylate, and octyl cyanoacrylate; methoxyethyl cyanoacrylate, ethoxyethyl cyanoacrylate, etc. Usually, ethyl cyanoacrylate is often used.
[0056] <Water content>
[0057] The moisture content of the methacrylic resin is preferably 0.01% or more and 1% or less. If the moisture content is to be suppressed to a lower level, it will be necessary to dry for a long time. From the viewpoint of productivity, it is preferably 0.01% or more. On the other hand, when it exceeds 1%, the storage stability after being dissolved in cyanoacrylate such as ethyl cyanoacrylate tends to deteriorate, so it is preferably 1% or less. It is more preferably 0.01% or more and 0.8% or less, further preferably 0.02% or more and 0.7% or less, and most preferably more than 0.03% and less than 0.7%.
[0058] Here, the moisture content can be measured by the method described in the examples below and by a drying method. 10.0 g of methacrylic resin is kept at 70° C. and the measurement is terminated when the weight loss rate in 10 seconds is 0.02% or less. The total weight loss rate is recorded as the moisture content.
[0059] The water content of the methacrylic resin (for example, methacrylic resin in the form of particles or beads) can be adjusted by, for example, drying the slurry after polymerization.
[0060] Examples of methods for drying the methacrylic resin include hot air drying in which hot air is sent from a hot air blower or a blower heater into a tank to dry the resin, vacuum drying in which the system is depressurized and then heated as necessary to dry the resin, drum drying in which the obtained polymer is rotated in a container to remove moisture, spin drying in which centrifugal force is used to dry the resin, air flow drying in which the resin is dried while being sent through a pipe with hot air, and a fluidized bed dryer in which the bottom of the tank is opened and closed after drying at a specific temperature for a certain period of time to allow the resin to fall into the next drying tank.
[0061] In order to make the moisture content within the above range, it is preferred that after the suspension polymerization, the obtained slurry is dried with a pneumatic dryer and / or a fluidized bed dryer. In this case, since the final moisture content is low, the processing takes time and the productivity is poor. In addition, problems such as poor pumping may occur in the slurry liquid feeding process.
[0062] <Weight average molecular weight>
[0063] The weight average molecular weight of the methacrylic resin measured by gel permeation chromatography (GPC) is preferably 85,000 to 1,500,000. From the viewpoint of mechanical strength and the amount of resin used when used as an adhesive, it is preferably 85,000 or more. When it is less than 85,000, since the amount of methacrylic resin used to make the slurry reach a specified viscosity increases, it is not preferred to affect the mechanical properties of the obtained adhesive, etc. when used as a thickener. In addition, from the viewpoint of solubility or characteristic stability when used as a thickener, it is preferably 1,500,000 or less. Regarding the particularly preferred molecular weight, although it depends on the desired viscosity and required characteristics when dissolved, it is preferably 85,000 or more and less than 300,000 when used at a relatively low viscosity or when the dissolution rate is to be increased. On the other hand, when used at a high viscosity or when a small amount of addition is required to obtain the desired viscosity, it is preferably 300,000 or more and 1,500,000 or less.
[0064] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the methacrylic resin measured by gel permeation chromatography (GPC) is preferably 1.7 or more and 2.5 or less. From the viewpoint of ease of manufacture, it is more preferably 1.8 or more. In addition, from the viewpoint of suppressing the dissolution residue during dissolution and improving the solubility, it is more preferably less than 2.5, further preferably less than 2.4, particularly preferably less than 2.3, and particularly preferably less than 2.3.
[0065] It should be noted that the weight average molecular weight and number average molecular weight are measured by GPC. A standard methacrylic resin that can be obtained as a reagent with a known monodisperse weight average molecular weight and an analytical gel column eluted from a high molecular weight component are used in advance, and a calibration curve is prepared according to the elution time and the weight average molecular weight. The molecular weight of each sample can be measured by the calibration curve. Specifically, it can be measured by the method described in the embodiments described below.
[0066] The shape of the methacrylic resin is not particularly limited, but is preferably in the form of pellets, flakes, beads or powder. From the viewpoint of shortening the dissolution time or reducing unmelted matter, beads or powder are preferred.
[0067] <Volume average particle size>
[0068] The volume average particle size of the methacrylic resin when used in the form of beads is preferably 100 to 500 μm. Since the smaller the particle size, the shorter the dissolution time, it is preferably 450 μm or less, and from the perspective of suppressing the scattering of beads during operation and reducing unmelted matter, it is preferably 100 μm or more. The volume average particle size is more preferably 150 to 400 μm, and most preferably 160 to 350 μm.
[0069] In this specification, the volume average particle size refers to a volume particle size that can be measured by the method described in Examples described later.
[0070] The standard deviation (SD value) of the volume particle size of the methacrylic resin is preferably 40 to 180 μm, more preferably 60 to 180 μm. By setting the standard deviation within the above range, polymerization control is easy, and when washing the polymerized beads, pipe clogging can be prevented during slurry transportation, etc., and dissolution residues when the cyanoacrylate is dissolved can be prevented. It is more preferably 60 to 150 μm, more preferably 60 to 140 μm, and even more preferably 70 to 135 μm.
[0071] Here, the SD value is represented by the following formula and can be measured by the method described in Examples below.
[0072] [Number 1]
[0073]
[0074] In the above formula, xi is the volume particle size, x-(mean value of x (xbar)) is the volume average particle size, and fi is the volume frequency of xi in laser scattering.
[0075] The 10% volume particle size D10 of the methacrylic resin is preferably 50 to 300 μm, more preferably 70 to 250 μm.
[0076] Methods for making the standard deviation of volume particle size and 10% volume particle size D10 within these ranges include using a suspending agent with an average particle size of 10 to 40 μm during polymerization, adjusting the pH of the suspending agent and the aqueous phase to a range of 4 to 7, preheating the suspending agent to 50°C to 90°C and then adding it to water (50°C to 90°C) in a polymerization reactor, appropriately adjusting the stirring speed, etc. It is preferred to combine a plurality of these.
[0077] The mass ratio of particles having a particle size of 710 μm or more relative to 100 mass% of the methacrylic resin (preferably methacrylic resin beads) is preferably 5 mass% or less, more preferably 3 mass% or less, further preferably 1 mass% or less, particularly preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less, from the viewpoint of obtaining high solubility in alkyl cyanoacrylate. The mass ratio of particles having a particle size of 710 μm or more can be measured, for example, by the method described in the Examples below.
[0078] <Polymerization method>
[0079] The methacrylic resin can be produced, for example, using a monomer constituting the methacrylic resin, a polymerization initiator, a chain transfer agent, a suspending agent, other additives, and the like.
[0080] As the above-mentioned polymerization initiator, when free radical polymerization is used, di-tert-butyl peroxide, lauryl peroxide, dilauroyl peroxide, tert-butyl peroxy 2-ethylhexanoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane and other peroxide-based or azo-based general free radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile) can be used, and these can be used alone or in combination of two or more. These free radical initiators can be combined with an appropriate reducing agent and implemented as a redox-based initiator.
[0081] The above-mentioned polymerization initiator is usually used in an amount within a range of 0.001 to 1% by mass based on 100% by mass of the total mass of the monomers.
[0082] In the method for producing the methacrylic resin, when producing the methacrylic resin by a radical polymerization method, a generally used chain transfer agent can be used to adjust the molecular weight.
[0083] As the chain transfer agent, for example, mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane trithioglycolate, and pentaerythritol tetrakis(thioglycolate) are preferably used.
[0084] The chain transfer agent can be used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers. The amount of the chain transfer agent is determined based on the desired molecular weight.
[0085] As the polymerization method of the methacrylic resin, suspension polymerization or emulsion polymerization is preferably used. In order to obtain granular resin beads in suspension polymerization and powdery resin beads in emulsion polymerization, it is advantageous in operation to dissolve an appropriate amount of a thickener for adjusting the slurry to a desired viscosity.
[0086] Since the polymerization time of suspension polymerization is shorter than that of emulsion polymerization, suspension polymerization is preferred.
[0087] In particular, when the suspension polymerization method is used for the above-mentioned methacrylic resin, it is preferable to make the molecular weight distribution within the above-mentioned range. When it is required to suppress the generation of unmelted matter due to the wide molecular weight distribution when dissolving in alkyl cyanoacrylate etc. at a high level and to maintain high storage stability after dissolution, it is preferable to obtain it by a one-stage suspension polymerization rather than a multi-stage polymerization having a wider molecular weight distribution.
[0088] In addition, as a polymerization method of the methacrylic resin, it is preferable to use a method of dispersing a suspending agent having an average particle size of 10 to 40 μm in water and polymerizing. Among them, it is preferable to disperse a suspending agent having an average particle size of 10 to 40 μm in water and perform a one-stage suspension polymerization.
[0089] In the method for producing the methacrylic resin, it is preferred that the average particle size of the suspending agent dispersed in the suspension polymerization water is 10 to 40 μm. This can control the standard deviation of the volume particle size of the methacrylic resin (e.g., methacrylic resin beads), stabilize the polymerization behavior, reduce the slow heating amount, and improve productivity.
[0090] The average particle size of the suspending agent can be adjusted by appropriately selecting the particle size of the suspending agent used. In addition, a suspending agent having an appropriate average particle size can be obtained by mixing powders having different particle sizes.
[0091] In the method for producing a methacrylic resin, the pH of the aqueous phase is preferably adjusted to a range of 4 to 7. By adjusting the pH to be within this range, the standard deviation of the bead particle size can be controlled and the polymerization behavior can be stabilized.
[0092] In the above method for producing methacrylic resin, it is preferred that the suspending agent is heated to 50°C to 90°C before being added to water (50°C to 90°C) in the reactor. This allows the average particle size of the methacrylic resin (eg, methacrylic resin beads) and its variation to be adjusted.
[0093] According to the manufacture method of the above-mentioned methacrylic resin, it is more preferable to use an inorganic suspending agent than an organic suspending agent. In the case of an organic suspending agent, there is a tendency that the mean particle size deviation of beads becomes too small. Here, as an organic suspending agent, polyvinyl alcohol, methylcellulose, ethylcellulose, hydroxypropyl methylcellulose, carboxymethylcellulose, gelatin, polyvinyl acetate etc. can be enumerated.
[0094] As the above-mentioned inorganic suspending agent, in consideration of stability after dissolution in alkyl cyanoacrylate, it is preferred to include an inorganic compound containing calcium and / or aluminum, for example, inorganic compounds such as calcium phosphate such as tricalcium phosphate (tertiary calcium phosphate), calcium carbonate, and aluminum hydroxide can be cited. In particular, from the viewpoint of stability after dissolution, it is more preferred to include an inorganic compound containing aluminum.
[0095] The suspending agent may further contain a suspending aid such as polyethylene glycol, sodium ethylenediaminetetraacetate, sodium lauryl sulfate, etc. The suspending aid may be contained in an amount of 0.01 to 10% by mass relative to 100% by mass of the suspending agent.
[0096] The above-mentioned suspending agent is preferably mixed with the monomer raw material in water and used.
[0097] <Cleaning method>
[0098] In the above-mentioned method for producing methacrylic resin, in order to remove the suspending agent, it is preferred to perform acid washing, water washing, alkali washing, etc. The number of times these washing operations are performed can be selected optimally according to the operating efficiency and the efficiency of removing the suspending agent, and can be once or repeatedly.
[0099] The washing temperature may be selected to be the optimum temperature in consideration of the removal efficiency of the suspending agent and the degree of coloration of the obtained polymer, and is preferably 20 to 100°C, more preferably 30 to 95°C, further preferably 40 to 95°C, and particularly preferably 50 to 80°C.
[0100] The washing time per washing is preferably 10 to 180 minutes, more preferably 20 to 150 minutes, from the viewpoints of washing efficiency, reduction of odor when used as a thickener, and solubility stability in cyanoacrylate.
[0101] The pH of the cleaning solution used during cleaning can be within the range that can remove the suspending agent, and the preferred pH is 1 to 12. The pH during acid cleaning is preferably 1 to 5, and more preferably 1.2 to 4, from the perspective of the removal efficiency of the suspending agent or the color tone of the obtained polymer. As the acid used at this time, there is no particular regulation as long as it can remove the suspending agent, and the existing well-known inorganic acids and organic acids can be used. An example of an acid preferably used is listed. As an inorganic acid, hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, boric acid, etc. can be cited, and a dilute solution diluted with water or the like can be used. As an organic acid, organic acids having a carboxyl group, a sulfonic group, a hydroxyl group, a thiol group, and an enol group can be cited. Considering the removal effect of the suspending agent or the color tone of the obtained resin, nitric acid, sulfuric acid, and an organic acid having a carboxyl group are more preferred.
[0102] After acid washing, it is preferred to further perform water washing or alkali washing from the viewpoint of suppressing residual dissolution when dissolving in cyanoacrylate. A method of washing in warm water at 50°C or higher is more preferred, and a method of washing in warm water at 50°C or higher and then performing alkali washing and / or washing in warm water at 50°C or higher is further preferred.
[0103] By adjusting the pH of the slurry after washing to 2 or more and 9 or less, preferably 4 or more and 7 or less, more preferably 5 or more and 6.8 or less, and particularly preferably 5.5 or more and 6.5 or less, a thickener having excellent storage stability when dissolved in cyanoacrylate and excellent light resistance can be obtained.
[0104] (additive)
[0105] The thickener of the present embodiment may optionally contain other additives. The additives are not particularly limited as long as they can exert the effects of the present invention, and may be appropriately selected according to the purpose.
[0106] The additives include, but are not limited to, various stabilizers such as ultraviolet absorbers, heat stabilizers, and light stabilizers; plasticizers; flame retardants; flame retardant aids; curing agents; curing accelerators; antistatic agents; conductivity-imparting agents; stress relaxants; mold release agents; crystallization accelerators; hydrolysis inhibitors; lubricants; impact-imparting agents; slip improvers; compatibilizers; nucleating agents; reinforcing agents such as fillers; flow regulators; dyes; sensitizers; colorants; anti-settling agents; anti-sagging agents; fillers; defoaming agents; light-diffusing microparticles; rust inhibitors; antibacterial / antifungal agents; antifouling agents; conductive polymers, etc.
[0107] <Heat stabilizer>
[0108] The heat stabilizer preferably used is not limited to the following, and examples thereof include hindered phenol antioxidants, phosphorus antioxidants, sulfur antioxidants, etc. These antioxidants may be used alone or in combination of two or more.
[0109] The content of the heat stabilizer may be an amount sufficient to obtain the effect of improving the thermal stability. If the content is excessive, there is a risk of precipitation during dissolution. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, further more preferably 0.8 part by mass or less, further preferably 0.01 to 0.8 part by mass, and particularly preferably 0.01 to 0.5 part by mass, based on 100 parts by mass of the methacrylic resin.
[0110] <Ultraviolet light absorber>
[0111] The ultraviolet absorber is not limited to the following, and examples thereof include benzotriazole compounds, benzotriazine compounds, benzoate compounds, benzophenone compounds, oxybenzophenone compounds, phenol compounds, oxazole compounds, malonate compounds, cyanoacrylate compounds, lactone compounds, salicylate compounds, and benzoxazinone compounds.
[0112] The melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, further preferably 130° C. or higher, and further more preferably 160° C. or higher.
[0113] When the temperature is increased from 23°C to 260°C at a rate of 20°C / min, the mass reduction ratio of the above-mentioned ultraviolet absorber is preferably 50% or less, more preferably 30% or less, further preferably 15% or less, further more preferably 10% or less, and further preferably 5% or less.
[0114] The content of the ultraviolet absorber may be an amount that can exert the effects of the present invention. However, if the amount added is too large, there is a possibility that the ultraviolet absorber will precipitate when dissolved as a binder. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 2.5 parts by mass or less, further more preferably 2 parts by mass or less, and further preferably 1.8 parts by mass or less, based on 100 parts by mass of the methacrylic resin. In addition, from the viewpoint of exerting the effect of the combination, it is preferably 0.01 parts by mass or more.
[0115] The thickener of the present embodiment may be the methacrylic resin obtained by the above method as it is, or may be mixed with other methacrylic resin compositions to form a thickener.
[0116] The thickener of this embodiment can be particularly suitable for use as a cyanoacrylate (preferably alkyl cyanoacrylate, more preferably ethyl cyanoacrylate) thickener.
[0117] The mass ratio of the methacrylic resin in the thickener is preferably 80 to 100 mass %, more preferably 90 to 100 mass %, and particularly preferably 99 to 100 mass %, based on 100 mass % of the thickener.
[0118] <Weight average molecular weight>
[0119] The weight average molecular weight of the thickener measured by gel permeation chromatography (GPC) is preferably 85,000 to 1,500,000. From the viewpoint of mechanical strength and the amount of resin used when used as an adhesive, it is preferably 85,000 or more. When it is less than 85,000, the amount of thickener used to make the slurry reach a specified viscosity increases, so it sometimes affects the mechanical properties of the obtained adhesive, etc., so it is not preferred. In addition, from the viewpoint of solubility or characteristic stability, it is preferably 1,500,000 or less. Regarding the particularly preferred molecular weight, although it depends on the desired viscosity and required characteristics when dissolved, it is preferably 85,000 or more and less than 300,000 when used at relatively low viscosity or when the dissolution rate is to be increased. On the other hand, when used at high viscosity or when a small amount of addition is required to obtain the desired viscosity, it is preferably 300,000 or more and 1,500,000 or less.
[0120] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the thickener measured by gel permeation chromatography (GPC) is preferably 2.5 or less, more preferably 1.7 or more and 2.5 or less. From the viewpoint of ease of manufacture, it is more preferably 1.8 or more. In addition, from the viewpoint of suppressing the dissolution residue during dissolution and improving solubility, it is more preferably less than 2.5, further preferably less than 2.4, particularly preferably less than 2.3, and particularly preferably less than 2.3.
[0121] In addition, the weight average molecular weight and the number average molecular weight can be measured by GPC, and specifically, can be measured by the method described in Examples described later.
[0122] <Dissolution stability>
[0123] The above-mentioned thickener (preferably a thickener containing the above-mentioned methacrylic resin having a weight average molecular weight of not less than 85,000 and less than 300,000) preferably satisfies 1.0<η2 / η1<5.0, when the viscosity of the thickener measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 20% by mass at 50°C is denoted as η1, and the viscosity of the thickener measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 20% by mass at 60°C for 48 hours is denoted as η2.
[0124] Here, leaving the sample at 60° C. for 48 hours means that the time elapsed from the time of placing the sample in the oven at 60° C. is between 46 hours and 50 hours.
[0125] By setting η2 / η1 within the above range, even when the thickener is dissolved in the alkyl cyanoacrylate and then left at room temperature for a long period of time (eg, several months), the viscosity and adhesive properties can be maintained.
[0126] Methods for adjusting η2 / η1 to a value greater than 1.0 and less than 5.0 include copolymerizing a certain amount of alkyl (meth)acrylate monomer units having an alkyl group with 4 or more carbon atoms, adjusting the moisture content of the methacrylic resin, making the standard deviation of the particle size within a certain range, reducing the weight proportion of particles with a particle size of 710 μm or more, and preferably combining a plurality of these.
[0127] Preferably, 1.0<η2 / η1<4.5, more preferably 1.0<η2 / η1<4.0. When it is less than 1.0, the viscosity decreases after dissolution and the thickener effect cannot be exerted, so it is not preferred. When it is more than 5, there is a concern that it may solidify in long-term storage such as several months or when the temperature rises during transportation, and the strength as an adhesive after solidification deteriorates, so it is not preferred.
[0128] When the thickener contains the methacrylic resin having a weight average molecular weight in the range of 300,000 to 1,500,000, the viscosity measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 10% by mass is denoted as η3, and the viscosity measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 10% by mass and left to stand at 60°C for 48 hours is denoted as η4, preferably satisfying 1.0<η4 / η3<5.0.
[0129] By keeping the content within this range, even when the thickener is dissolved in the alkyl cyanoacrylate and then left at room temperature for a long period of time (several months), the viscosity and adhesive properties can be maintained.
[0130] Preferably, 1.0<η4 / η3<4.5, more preferably, 1.0<η4 / η3<4.0.
[0131] When the ratio is below 1.0, the viscosity decreases after dissolution and the effect as a thickener cannot be exerted, so it is not preferred. When it is above 5, it is worried that it will solidify under the conditions of long-term storage such as several months or temperature rise during transportation, and the strength variation as an adhesive after solidification is poor, so it is not preferred.
[0132] It should be noted that the above-mentioned viscosities η1, η2, η3, and η4 can be measured by the method described in the examples described later.
[0133] <MMA Volatilization Amount>
[0134] From the viewpoint of suppressing odor, the MMA volatilization amount of the thickener when 5 mg of the thickener is heated at 60° C. for 10 minutes is preferably 10 mass ppm or less, more preferably 5 mass ppm or less, and even more preferably 1 mass ppm or less.
[0135] The MMA volatilization amount when 5 mg of the methacrylic resin contained in the thickener is heated at 60° C. for 10 minutes is preferably 10 mass ppm or less, more preferably 5 mass ppm or less, and even more preferably 1 mass ppm or less.
[0136] As a method for adjusting the volatility to this range, for example, there is a method of drying the slurry obtained in the polymerization under air flow at a temperature of 100° C. or higher, preferably 120° C. or higher. The MMA volatility can be measured by pyrolysis GC / MS.
[0137] <YI value of acetone solution>
[0138] The thickener is preferably dissolved in acetone at a concentration of 10% by mass and the YI value measured using a cuvette having a thickness of 1 cm is 0.1 to 2, more preferably 0.2 to 1.9, and even more preferably 0.3 to 1.8.
[0139] The YI value of the methacrylic resin contained in the thickener measured by dissolving it in acetone at a concentration of 10% by mass using a cuvette having a thickness of 1 cm is preferably 0.1 to 2, more preferably 0.2 to 1.9, and even more preferably 0.3 to 1.8.
[0140] By setting the YI value within the above range, a pressure-sensitive adhesive having excellent hue and light resistance can be obtained. As a method for setting the YI value within the above range, there is a method of obtaining a methacrylic resin by one-stage polymerization instead of two-stage polymerization.
[0141] <pH when the thickener is dispersed in water>
[0142] The pH of the supernatant aqueous phase measured at room temperature after stirring and dispersing 20 g of the thickener and 100 g of pure water and allowing the solid content to settle is preferably 2 or more and 9 or less. From the viewpoint of maintaining a particularly good hue when the thickener is dissolved and used, solubility in cyanoacrylate, and suppressing odor from residual substances, it is more preferably 3 or more, and particularly preferably 3.5 or more. From the viewpoint of improving storage stability after dissolving in cyanoacrylate or the like, it is preferably 8.5 or less, more preferably 8 or less, and particularly preferably 7.5 or less.
[0143] In addition, the pH of the supernatant aqueous phase measured at room temperature after stirring and dispersing 20 g of the methacrylic resin contained in the thickener and 100 g of pure water and allowing the solid content to settle is preferably 2 or more and 9 or less. From the viewpoint of maintaining a particularly good hue when the thickener is dissolved and used, solubility in cyanoacrylate, and suppressing odor from residual substances, it is more preferably 3 or more, and particularly preferably 3.5 or more. From the viewpoint of improving storage stability after dissolving in cyanoacrylate, etc., it is preferably 8.5 or less, more preferably 8 or less, and particularly preferably 7.5 or less.
[0144] <Mass ratio of particles with a particle size of 710 μm or more>
[0145] The mass ratio of particles having a particle size of 710 μm or more relative to 100 mass% of the thickener is preferably 5 mass% or less, more preferably 3 mass% or less, further preferably 1 mass% or less, particularly preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less, from the viewpoint of obtaining high solubility in the cyanoacrylate adhesive. The mass ratio of particles having a particle size of 710 μm or more can be measured, for example, by the method described in the Examples below.
[0146] [Adhesive]
[0147] The adhesive of the present embodiment includes the thickener containing the methacrylic resin and cyanoacrylate (preferably alkyl cyanoacrylate), and may further contain the additives described above.
[0148] The above-mentioned adhesive may be composed only of the above-mentioned thickener and alkyl cyanoacrylate.
[0149] The viscosity of the adhesive at 25° C. is preferably 0.5 to 10 Pa·s. Here, the viscosity is measured using a B-type viscometer.
[0150] It is more preferably 1 to 9 Pa·s, and further preferably 2 to 8 Pa·s. By keeping it within this range, an adhesive with excellent handling properties can be obtained. As a method for adjusting the viscosity of the adhesive to the above range, there can be mentioned adjusting the weight average molecular weight of the methacrylic resin, adjusting the concentration of the methacrylic resin or the thickener in the adhesive, etc. Specifically, when using a methacrylic resin with a high weight average molecular weight, the concentration can be reduced, and when using a methacrylic resin with a low weight average molecular weight, the concentration can be increased. Generally, a high weight average molecular weight can reduce the amount of addition and is therefore preferred, but there are cases where it takes time to dissolve a high molecular weight methacrylic resin, and it can be appropriately set according to the required characteristics as an adhesive.
[0151] As a specific concentration, the methacrylic resin having a weight average molecular weight of 85,000 or more and less than 300,000 is preferably dissolved in cyanoacrylate (preferably alkyl cyanoacrylate, more preferably ethyl cyanoacrylate) at a mass percentage concentration of 10 to 30%, more preferably at a mass percentage concentration of 12 to 28%, and further preferably at a mass percentage concentration of 15 to 25%, relative to 100% by mass of the adhesive.
[0152] The methacrylic resin having a weight average molecular weight of 300,000 to 1,500,000 is preferably dissolved in cyanoacrylate (preferably alkyl cyanoacrylate, more preferably ethyl cyanoacrylate) at a mass percentage concentration of 1% to 20%, more preferably 3 to 18%, and further preferably 5 to 15%, relative to 100% by mass of the adhesive.
[0153] The temperature during dissolution is preferably 30° C. or higher from the viewpoint of easy solubility, and is preferably 80° C. or lower from the viewpoint of stability.
[0154] Example
[0155] The following examples and comparative examples will be used to explain the present invention in more detail.
[0156] <Raw materials>
[0157] The raw materials used are as follows.
[0158] Methyl methacrylate (MMA): manufactured by Asahi Kasei (2.5 ppm by mass of 2,4-dimethyl-6-tert-butylphenol manufactured by Chugai Trading was added as a polymerization inhibitor).
[0159] Methyl acrylate (MA): manufactured by Mitsubishi Chemical (containing 15 ppm of 4-methoxyphenol as a polymerization inhibitor).
[0160] Butyl acrylate (BA): manufactured by Toagosei Co., Ltd. (containing 15 ppm by mass of 4-methoxyphenol as a polymerization inhibitor).
[0161] Ethylhexyl acrylate (EHA): manufactured by Tokyo Chemical Industry.
[0162] n-Octyl mercaptan (NOM): manufactured by Arkema.
[0163] 2-Ethylhexyl thioglycolate (EHTG): manufactured by Arkema.
[0164] Lauroyl peroxide (LPO): manufactured by NOF Corporation.
[0165] Calcium phospate: manufactured by Nippon Chemical Industry.
[0166] Calcium carbonate: manufactured by Nitto Powder Industry Co., Ltd., NN#200, average particle size 14.8 μm.
[0167] Sodium lauryl sulfate: manufactured by Wako Pure Chemical Industries, used as a suspending aid.
[0168] Tetrasodium ethylenediaminetetraacetate dihydrate (EDTA): manufactured by Kishida Chemical.
[0169] Aluminum hydroxide: SBX73, B303, B153, and B103 manufactured by Nippon Light Metal Co., Ltd. were used, and the average particle size was adjusted by appropriately mixing each of them.
[0170] [I. Production of thickener]
[0171] (Example 1)
[0172] -Suspension Concentrate-
[0173] In a container having a stirrer equipped with four inclined blades, 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 33 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added and stirred to obtain a mixed solution (a2). The average particle size of the suspending agent in the mixed solution (a2) was 33 μm, and the pH of the obtained mixed solution was 5.5. The obtained mixed solution (a2) was heated to 70°C.
[0174] Next, 25 kg of water was added to a 60 L reactor and the temperature was raised to 80° C., and a mixed solution of 3 kg of the above suspension agent mixture (a2), 21 kg of monomer raw materials in the mixing ratio shown in Table 1, 60 g of EHTG, and 43 g of LPO was added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and an exothermic peak was observed 140 minutes after the start of the monomer addition.
[0175] Thereafter, the temperature was raised to 93° C. at a rate of 1° C. / min and the temperature was maintained at about 93° C. for 45 minutes, thereby substantially completing the polymerization reaction and obtaining a polymer slurry.
[0176] Next, the mixture was cooled to 50°C and 20% by mass sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was filtered through a filter cloth after removing aggregates through a 1.68 mm mesh sieve to separate the bead-like methacrylic resin particles and the suspended waste liquid. The pH of the suspended waste liquid was 3.3 at this time.
[0177] Thereafter, add ion exchange water heated to about 70°C in an amount substantially equal to that of the bead polymer, stir, wash, and filter, and similarly perform the washing operation with ion exchange water at about 70°C again to obtain a slurry polymer solution (two water washings in total). To the obtained slurry polymer solution, add dropwise an aqueous sodium hydroxide solution to adjust the pH to 8.5, and stir and wash. When filtering with filter cloth, and further adding ion exchange water heated to 70°C and stirring and washing, the pH of the obtained slurry polymer solution is 6.1. Thereafter, filter with filter cloth to obtain resin beads. The undried resin beads obtained are dried in an air flow dryer at an air flow of 150°C (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 / hr) and dried at 90°C for 5 minutes to obtain methacrylic resin beads. The weight average molecular weight of the obtained beads was 142,000, and Mw / Mn=1.9. The results of NMR (manufactured by JEOL Ltd., JNM-ECA500) confirmed that a methacrylic resin having the same composition as that of the raw material was obtained.
[0178] (Example 2)
[0179] The suspension mixture (a2) was prepared in the same manner as in Example 1.
[0180] Next, 25 kg of water was added to a 60 L reactor and the temperature was raised to 80° C., and a mixed solution of 3 kg of the above suspension agent mixture (a2) and 21 kg of monomer raw materials, 60 g of EHTG, and 43 g of LPO in the proportions shown in Table 1 was added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and an exothermic peak was observed 140 minutes after the start of the monomer addition.
[0181] Thereafter, the temperature was raised to 93° C. at a rate of 1° C. / min and the temperature was maintained at about 93° C. for 45 minutes, thereby substantially completing the polymerization reaction and obtaining a polymer slurry.
[0182] Next, the mixture was cooled to 50°C and 20% by mass sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was filtered through a filter cloth after removing aggregates through a 1.68 mm mesh sieve to separate the bead-like methacrylic resin particles and the suspended waste liquid. The pH of the suspended waste liquid was 3.3 at this time.
[0183] Thereafter, an amount of ion exchange water heated to about 70°C substantially equal to that of the bead polymer was added, followed by stirring, washing, and filtering. Similarly, the washing operation with ion exchange water at about 70°C was repeated twice to obtain a slurry polymer solution (three water washings in total). The pH of the obtained slurry polymer solution was 6.0. Thereafter, the resin beads were obtained by filtering with a filter cloth. The obtained undried resin beads were dried in an air flow dryer at 150°C (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 The methacrylic resin beads were obtained by drying at 90°C for 5 minutes at a rate of 1:100 / hr. The obtained beads had a weight average molecular weight of 136,000 and Mw / Mn=2.0.
[0184] (Example 3, Comparative Examples 1 and 2)
[0185] Except for polymerizing with the composition described in Table 1, the same procedure as in Example 1 was carried out to obtain methacrylic resin beads.
[0186] (Example 4)
[0187] Methacrylic resin beads were obtained by the same composition and polymerization method as in Example 1 except that the temperature of the air flow dryer was set to 100°C.
[0188] (Example 5)
[0189] -Suspension Concentrate-
[0190] In a container having a stirrer equipped with four inclined blades, 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 23 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added and stirred to obtain a mixed solution (a2). The average particle size of the suspending agent in the mixed solution (a2) was 23 μm, and the pH of the obtained mixed solution was 5.5. The obtained mixed solution (a2) was heated to 70°C.
[0191] 27 kg of water, 3 kg of the suspending agent prepared in the same manner as in Example 1, 16 kg of the monomer raw materials in the proportion shown in Table 2, 13 g of EHTG, and 25 g of LPO were added to a 60 L reactor and stirred and mixed. The reaction temperature of the reactor was 80° C. and polymerized for 150 minutes. Thereafter, the temperature was raised to 93° C. at a rate of 1° C. / min, and the mixture was aged for 45 minutes to substantially terminate the polymerization reaction and obtain a polymer slurry. Subsequently, the mixture was cooled to 50° C. and 20% by mass sulfuric acid was added to dissolve the suspending agent.
[0192] Next, after removing the aggregates from the polymerization reaction solution through a sieve with a mesh size of 1.68 mm, the obtained suspension was filtered through a filter cloth to separate the bead-like methacrylic resin particles and the suspended waste liquid. Thereafter, the same operation as in Example 1 was performed after adding ion exchange water heated to 70° C. in an amount substantially equal to that of the bead-like polymer to obtain resin beads. The weight average molecular weight of the obtained resin beads was 402,000, and Mw / Mn=2.2.
[0193] (Example 6)
[0194] Methacrylic resin beads were obtained by the same composition and polymerization method as in Example 5 except that the amount of EHTG in the monomer raw material was 8 g. The time from the addition of the monomer to the observation of the exothermic peak was 120 minutes. The weight average molecular weight of the obtained resin beads was 654,000, and Mw / Mn=2.2.
[0195] (Example 7)
[0196] Methacrylic resin beads were obtained by the same composition and polymerization method as in Example 5, except that the amount of water used was 30 kg and EHTG was not added for polymerization. The time from the addition of the monomer to the observation of the exothermic peak was 100 minutes. The weight average molecular weight of the obtained resin beads was 1.25 million, and Mw / Mn=2.4.
[0197] (Example 8, Comparative Examples 3 and 4)
[0198] Methacrylic resin beads were obtained in the same manner as in Example 1 except that ethylhexyl acrylate or methyl acrylate was used instead of BA.
[0199] (Example 9)
[0200] A polymer slurry was obtained by the same composition and polymerization method as in Example 1. Then, the mixture was cooled to 50°C and 20% by mass sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was filtered through a filter cloth after removing coagulations with a 1.68 mm mesh sieve to separate the bead-like methacrylic resin particles and the suspended waste liquid.
[0201] After that, the pH of the slurry was 4.6 when the ion exchange water at room temperature (about 25°C) was added in an amount substantially equal to that of the bead polymer and stirred and washed. The resin beads were filtered with a filter cloth to obtain the resin beads. The obtained undried resin beads were dried in an air flow dryer at 150°C (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 / hr) and dried at 90°C for 5 minutes to obtain methacrylic resin beads.
[0202] (Example 10)
[0203] A polymer slurry was obtained by the same composition and polymerization method as in Example 3. Then, the mixture was cooled to 50°C and 20% by mass sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was filtered through a filter cloth after removing coagulations with a 1.68 mm mesh sieve to separate the bead-like methacrylic resin particles and the suspended waste liquid.
[0204] After that, room temperature water in an amount substantially equal to that of the beaded polymer was added, and then sodium hydroxide aqueous solution was added to adjust the pH to 10.5, followed by stirring, washing, and filtering with a filter cloth to obtain resin beads. The obtained undried resin beads were dried in an air flow dryer at 150°C (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 / hr) and dried at 90°C for 5 minutes to obtain methacrylic resin beads.
[0205] (Example 11) Polymerization Example of Two-stage Polymerization
[0206] Into a container equipped with a stirrer equipped with four inclined paddle blades, 2 kg of water, 65 g of the third calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate were added to obtain a suspension liquid (A).
[0207] Next, 26 kg of water was added to a 60 L reactor and the temperature was raised to 80° C. Then, the entire suspension liquid (A) and monomer raw materials prepared in advance including 3900 g of methyl methacrylate, 20 g of butyl acrylate, 42 g of EHTG, and 28 g of LPO were added.
[0208] The suspension polymerization was maintained at about 80°C for 150 minutes, and the reaction was substantially completed to obtain polymer (I). Thereafter, after stirring at 80°C for 60 minutes, a monomer raw material prepared by pre-blending 20 kg of methyl methacrylate, 100 g of butyl acrylate, 35 g of NOM, and 40 g of LPO was added to the reactor, and the suspension polymerization was continued at about 80°C for 90 minutes, and then the temperature was raised to 92°C at a rate of 1°C / min, and the temperature was maintained for 60 minutes to substantially complete the polymerization reaction.
[0209] Next, the mixture was cooled to 50°C and 20% by mass sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was filtered through a filter cloth after removing aggregates through a 1.68 mm mesh sieve to separate the bead-like methacrylic resin particles and the suspended waste liquid. The pH of the suspended waste liquid was 3.3 at this time.
[0210] Thereafter, add ion exchange water heated to about 70°C in an amount substantially equal to that of the bead polymer, stir, wash, and filter, and similarly perform the washing operation with ion exchange water at about 70°C again to obtain a slurry polymer solution (two water washings in total). To the obtained slurry polymer solution, add dropwise an aqueous sodium hydroxide solution to adjust the pH to 8.5, and stir and wash. When filtering with filter cloth, and further adding ion exchange water heated to 70°C and stirring and washing, the pH of the obtained slurry polymer solution is 6.1. Thereafter, filter with filter cloth to obtain resin beads. The undried resin beads obtained are dried in an air flow dryer at an air flow of 150°C (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 / hr) and dried at 90°C for 5 minutes to obtain methacrylic resin beads. The weight average molecular weight of the obtained beads was 124,000, and Mw / Mn=2.6.
[0211] [Comparative Example 5]
[0212] Into a container equipped with a stirrer equipped with four inclined paddle blades, 2 kg of water, 65 g of the third calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate were added to obtain a suspension liquid (A).
[0213] Next, 21 kg of water was added to a 60 L reactor and the temperature was raised to 80° C., and a mixed solution of the suspension liquid (A) and the monomer raw materials in the proportions shown in Table 3, as well as 60 g of EHTG and 63 g of LPO was added. Thereafter, suspension polymerization was carried out at about 80° C. for 110 minutes, and then the temperature was raised to 93° C. at a rate of 1° C. / min, and the temperature was maintained at about 93° C. for 45 minutes, substantially completing the polymerization reaction and obtaining a polymer slurry. In order to increase the amount of LPO as an initiator, the polymerization time was shortened.
[0214] Next, the mixture was cooled to 50° C. and 20% by mass sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was filtered through a filter cloth to separate into bead-like methacrylic resin particles and a suspended waste liquid. The pH of the suspended waste liquid was 3.3 at this time.
[0215] Thereafter, add ion exchange water heated to about 70°C in an amount substantially equal to that of the bead polymer, stir, wash, and filter, and similarly perform the washing operation with ion exchange water at about 70°C again to obtain a slurry polymer solution (two water washings in total). To the obtained slurry polymer solution, add dropwise an aqueous sodium hydroxide solution to adjust the pH to 8.5, and stir and wash. When filtering with filter cloth, and further adding ion exchange water heated to 70°C and stirring and washing, the pH of the obtained slurry polymer solution is 6.1. Thereafter, filter with filter cloth to obtain resin beads. The undried resin beads obtained are dried in an air flow dryer at an air flow of 150°C (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 The methacrylic resin beads were obtained by drying at 90°C for 5 minutes at a rate of 1000 μm / hr. The obtained beads had a particle size ratio of 5.1% of 710 μm or larger.
[0216] (Example 12)
[0217] -Suspension Concentrate-
[0218] In a container having a stirrer equipped with four inclined blades, 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 33 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added and stirred to obtain a mixed solution (a2). The average particle size of the suspending agent in the mixed solution (a2) was 33 μm, and the pH of the obtained mixed solution was 5.5. The obtained mixed solution (a2) was heated to 70°C.
[0219] Next, 25 kg of water was added to a 60 L reactor and the temperature was raised to 80° C., and a mixed solution of 3 kg of the above suspension agent mixture (a2), 21 kg of monomer raw materials in the mixing ratio shown in Table 1, 60 g of EHTG, and 43 g of LPO was added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and an exothermic peak was observed 140 minutes after the start of the monomer addition.
[0220] Thereafter, the temperature was raised to 93° C. at a rate of 1° C. / min and the temperature was maintained at about 93° C. for 45 minutes, thereby substantially completing the polymerization reaction and obtaining a polymer slurry.
[0221] Next, the mixture was cooled to 50°C and 20% by mass sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was filtered through a filter cloth after removing aggregates through a 1.68 mm mesh sieve to separate the bead-like methacrylic resin particles and the suspended waste liquid. The pH of the suspended waste liquid was 3.3 at this time.
[0222] Thereafter, add ion exchange water heated to about 70°C in an amount substantially equal to that of the bead polymer, stir, wash, and filter, and similarly perform the washing operation with ion exchange water at about 70°C again to obtain a slurry polymer solution (two water washings in total). To the obtained slurry polymer solution, add dropwise an aqueous sodium hydroxide solution to adjust the pH to 8.5, and stir and wash. When filtering with filter cloth, and further adding ion exchange water heated to 70°C, stirring, and washing, the pH of the obtained slurry polymer solution is 6.1. Thereafter, filter with filter cloth to obtain resin beads. The undried resin beads obtained are dried in an air flow dryer at 80°C with an air flow (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 The methacrylic resin beads were obtained by drying at 90°C for 5 minutes at a rate of 1:1 / hr. The obtained beads had a weight average molecular weight of 147,000 and Mw / Mn=1.8.
[0223] [II. Physical properties of methacrylic resin]
[0224] (II-1) (Weight average molecular weight, molecular weight distribution)
[0225] The weight average molecular weight and molecular weight distribution of the methacrylic resin beads obtained in Examples and Comparative Examples were measured using the following apparatus and conditions.
[0226] Measuring apparatus: Gel permeation chromatograph (HLC-83 20GPC) manufactured by Tosoh Corporation.
[0227] Column: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgelSuperH2500 were connected in series in this order and used.
[0228] In this column, high molecular weight elutes quickly, while low molecular weight elutes later.
[0229] Detector: RI (differential refractometer) detector.
[0230] Detection sensitivity: 3.0mV / min.
[0231] Column temperature: 40℃.
[0232] Sample: 0.02 g of methacrylic acid resin in 20 mL of tetrahydrofuran.
[0233] Injection volume: 10 μL.
[0234] Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min.
[0235] As an internal standard, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added.
[0236] As standard samples for calibration curve, the following 10 types of polymethyl methacrylates having known monodisperse peak top molecular weights and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.
[0237] Peak molecular weight (Mp) Standard sample 1 1916000 Standard sample 2 625500 Standard sample 3 298900 Standard sample 4 138600 Standard sample 5 60150 Standard sample 6 27600 Standard sample 7 10290 Standard sample 8 5000 Standard sample 9 2810 Standard sample 10 850
[0238] Under the above conditions, the RI detection intensity was measured with respect to the elution time of the methacrylic resin.
[0239] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin were determined based on the area of the region in the GPC elution curve and the calibration curve of the third-order approximation formula.
[0240] (II-2) (volume average particle size, D10)
[0241] The volume average particle size, SD value, 10% particle size and particle size of the suspending agent were measured using the laser scattering method of LS13320 manufactured by Beckman Coulter.
[0242] (II-3) (Measurement of moisture content)
[0243] Using a Shimadzu moisture balance MOC-120H, 10.0 g of beads were kept at 70°C. The measurement was terminated when the weight loss rate in 10 seconds was 0.02% or less, and the total weight loss rate was recorded as the moisture content.
[0244] (II-4) (Determination of volatile matter)
[0245] The MMA volatilization amount was measured using GC-6890 and MSD-5973 manufactured by Agilent. 5 mg of methacrylic acid resin was heated at 60°C for 10 minutes in a thermal cracking furnace, and the generated gas was trapped using a column HP5-MS cooled by liquid nitrogen. The trapped generated gas was analyzed by GC / MS to quantify the MMA volatilization amount.
[0246] (II-5) (Determination of YI value)
[0247] A solution of the obtained methacrylic resin dissolved in acetone at a mass percent concentration of 10% was added to a 1 cm thick cuvette, and the YI value was measured using a colorimeter (TC-8600A manufactured by Tokyo Denshoku Co., Ltd., light source: 10-C) in accordance with JIS K7105.
[0248] (II-6) (pH of aqueous phase during dispersion)
[0249] 20 g of methacrylic resin and 100 g of pure water were dispersed by stirring, and then allowed to stand to allow the solid content to settle, and then the pH was measured at room temperature.
[0250] Measuring equipment: pH meter F-52 (HORIBA).
[0251] Electrode: Standard ToupH electrode 9615S-10D.
[0252] (II-7) (Measurement of the content of particles larger than 710 μm)
[0253] About 100 g of methacrylic resin was used, and the weight of particles remaining on each sieve when sieving for 10 minutes under the condition of maximum vibration force (MAX) using sieves (JTS-200-45-31 (mesh aperture 710 μm), JTS-200-45-44 (mesh aperture 500 μm), 35 (mesh aperture 355 μm), 36 (mesh aperture 300 μm), 37 (mesh aperture 250 μm), 38 (mesh aperture 150 μm), 61 (receiving vessel) manufactured by Tokyo Screen) was measured based on JIS-Z8801, and the content of particles remaining on the sieve with a mesh aperture of 710 μm (content of particle size components of 710 μm or more) was measured. The measurement was carried out three times, and the content was calculated from the average value.
[0254] [710 μm and above content] = 100 × [weight of particles remaining on the sieve with a mesh size of 710 μm] / [weight of sample supplied to the sieve tester] (%)
[0255] (II-8) (Viscosity of slurry)
[0256] Add silicone oil to an oil bath with a stirrer and heat to 50°C. Add 16g of resin beads, 64g of ethyl cyanoacrylate (when the thickener is 20% by mass) and a rotor to a 110cc screw bottle (50mm in diameter), and close the lid of the screw bottle. Place the screw bottle in the oil bath, rotate the stirrer (150rpm), and dissolve the resin beads in ethyl cyanoacrylate. When 10% by mass, dissolve at a ratio of 8g of resin beads to 72g of ethyl cyanoacrylate.
[0257] For the case where the weight average molecular weight is 85,000 or more and less than 300,000, the viscosity η1 measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 20 mass % and cooled, and the viscosity η2 measured at 25°C after being left at 60°C for 48 hours are measured.
[0258] For those with a weight average molecular weight of 300,000 or more, the viscosity η3 measured at 25°C after being dissolved at a concentration of 10 mass % and cooled, and the viscosity η4 measured at 25°C after being left at 60°C for 48 hours were measured.
[0259] The viscosity was measured using a B-type viscometer (LVDV Next, a digital viscometer manufactured by Eikon Seiki). The slurry prepared by the method described in the above dissolution rate was cooled to 25°C. The slurry liquid was measured with a 40cc measuring tube, and the measuring tube was placed in the viscometer to start the viscosity measurement. The viscosity was measured at a rotor speed of 60 rpm (if the rotor speed exceeded the measurement range at 60 rpm, the speed was reduced for measurement).
[0260] For those with high viscosity, the amount added can be adjusted during the slurry preparation to achieve an appropriate viscosity.
[0261] Since the weight average molecular weight of Example 7 is as high as 1.25 million and the viscosity of the 10% solution is as high as 43 Pa·s, the 7% solution obtained a slurry with a viscosity of 5.4 Pa·s.
[0262] [III. Evaluation of thickener]
[0263] The methacrylic resin beads obtained in Examples and Comparative Examples were used as thickeners and the following evaluations were performed.
[0264] (III-1) (Smell)
[0265] 400 g of methacrylic resin was placed in a polymer container (closed type, 500 mL iboy (trademark) wide-mouth bottle), heated at 60°C for 2 hours, left to cool to 30°C, and then smelled and scored according to the following criteria.
[0266] 6: Unbearable smell.
[0267] 5: Very pungent smell.
[0268] 4: Pungent smell.
[0269] 3: Can be felt strongly but not pungent.
[0270] 2: Perceptible (slightly) but not pungent.
[0271] 1: It’s hard to feel.
[0272] The evaluation was conducted by 5 people and the average was as follows:
[0273] 2 or less: A (very good).
[0274] More than 2 and 3 or less: B (excellent).
[0275] More than 3 and less than 4: C (good).
[0276] More than 4: D (defective).
[0277] (III-2) (Dissolution rate)
[0278] Add silicone oil to an oil bath with a stirrer and heat to 50°C. Add 16g of thickener, 64g of ethyl cyanoacrylate monomer (when the thickener is 20wt%) and a rotor to a 110cc screw bottle (50mm in diameter), and close the lid of the screw bottle. Place the screw bottle in the oil bath, rotate the stirrer (150rpm) and start the measurement. Measure the time until the thickener in the bottle dissolves in the ethyl cyanoacrylate. When it is 10wt%, dissolve at a ratio of 8g of thickener to 72g of ethyl cyanoacrylate monomer.
[0279] Complete dissolution within 45 minutes: A (very good).
[0280] Completely dissolved within 60 minutes: B (excellent).
[0281] Dissolution took more than 60 minutes but was almost dissolved: C (good).
[0282] Unmelted matter was observed: D (bad).
[0283] (III-3) (Long-term stability after dissolution)
[0284] Methacrylic resin beads were dissolved in ethyl cyanoacrylate at 50° C. in the same manner as above. Resin beads having a weight average molecular weight of 85,000 or more and less than 300,000 were dissolved in ethyl cyanoacrylate at a concentration of 20% by mass, and resin beads having a weight average molecular weight of 300,000 or more were dissolved in ethyl cyanoacrylate at a concentration of 10% by mass, and then cooled, and the viscosity η5 measured at 25° C. and the viscosity η6 after standing at 25° C. for 90 days were determined.
[0285] When η6 / η5 is less than 5, the stability is A (very excellent); 5 or more and less than 10 is B (excellent); 10 or more and less than 20 is C (good); 20 or more is D (poor).
[0286] (III-4)(light resistance)
[0287] A portion of the sample dissolved in ethyl cyanoacrylate was extracted and placed in a transparent 100 mL container (sealed), and placed outdoors in direct sunlight for 1 month. After placement, the sample was considered poor (C) if it was cured, good (B) if it was not cured but its fluidity was significantly reduced, and excellent (A) if its fluidity was maintained.
[0288] [Table 1]
[0289]
[0290] [Table 2]
[0291]
[0292] [Table 3]
[0293]
[0294] Comparison between Examples 1 to 4 and Comparative Examples 1 to 4 shows that the odor of dissolved cyanoacrylate is reduced by containing a predetermined amount of an alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms.
[0295] In addition, when Example 1 and Example 11 are compared, it can be seen that since both copolymerize the (meth)acrylate monomer unit having an alkyl group with 4 or more carbon atoms, the odor of the cyanoacrylate after dissolution is reduced, but the single-stage polymerization product with a narrow molecular weight distribution has higher dissolution stability than the multi-stage polymerization product with a wide molecular weight distribution.
[0296] When comparing Example 1 with Examples 9 and 10, the pH of the aqueous phase is different when the thickener is dispersed in water. It is known that although all three have highly improved odor, Example 1 has a higher level of dissolution stability and light resistance.
[0297] Industrial Applicability
[0298] The thickener of the present invention improves odor and has excellent stability after the cyanoacrylate is dissolved, and has industrial applicability.
Claims
1. A thickener for a cyanoacrylate adhesive, characterized in that: The thickener for a cyanoacrylate adhesive includes a methacrylic resin containing 95 to 99.9% by mass of a methyl methacrylate monomer unit and 0.1 to 5% by mass of an alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms.
2. The thickener for a cyanoacrylate adhesive according to claim 1, wherein When 5 mg of the methacrylic resin is heated at 60° C. for 10 minutes, the amount of methyl methacrylate volatilized is 10 mass ppm or less.
3. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The mass ratio of particles having a particle size of 710 μm or more is 5 mass % or less relative to 100 mass % of the thickener for the cyanoacrylate adhesive.
4. The thickener for cyanoacrylate adhesive according to claim 2, wherein The mass ratio of particles having a particle size of 710 μm or more is 5 mass % or less relative to 100 mass % of the thickener for the cyanoacrylate adhesive.
5. The thickener for a cyanoacrylate adhesive according to any one of claims 1 to 4, wherein The pH when the thickener for cyanoacrylate adhesives is dispersed in water is 2.0 to 9.
0.
6. The thickener for a cyanoacrylate adhesive according to any one of claims 1 to 4, wherein The thickener for cyanoacrylate adhesives has a molecular weight distribution Mw / Mn of 2.5 or less.
7. The thickener for a cyanoacrylate adhesive according to claim 5, wherein The thickener for cyanoacrylate adhesives has a molecular weight distribution Mw / Mn of 2.5 or less.
8. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The thickener for a cyanoacrylate adhesive is composed only of a methacrylic resin containing 95 to 99.9% by mass of a methyl methacrylate monomer unit and 0.1 to 5% by mass of an alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms.
9. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The weight average molecular weight of the thickener for cyanoacrylate adhesives is 85,000 or more and 1,500,000 or less.
10. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The weight average molecular weight of the methacrylic resin contained in the thickener for the cyanoacrylate adhesive is 85,000 or more and less than 300,000. When the viscosity measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 20% by mass is referred to as η1, and the viscosity measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 20% by mass and left at 60°C for 48 hours is referred to as η2, the following formula is satisfied: 1.0<η2 / η1<5.
0.
11. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The weight average molecular weight of the methacrylic resin contained in the thickener for the cyanoacrylate adhesive is 300,000 or more and 1,500,000 or less, When the viscosity measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 10% by mass is referred to as η3, and the viscosity measured at 25°C after being dissolved in ethyl cyanoacrylate at a concentration of 10% by mass and left at 60°C for 48 hours is referred to as η4, the following formula is satisfied: 1.0<η4 / η3<5.
0.
12. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The (meth)acrylic acid alkyl ester monomer unit having an alkyl group with 4 or more carbon atoms is derived from n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, and 2-ethylhexyl methacrylate.
13. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The methacrylic resin is composed only of a methyl methacrylate monomer unit and an alkyl (meth)acrylate monomer unit having an alkyl group having 4 or more carbon atoms.
14. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The methacrylic resin further contains other vinyl monomer units copolymerizable with the methyl methacrylate.
15. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The water content of the methacrylic resin is 0.01% or more and 1% or less.
16. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The methacrylic resin is used in the form of beads, and the volume average particle size of the methacrylic resin is 100 to 500 μm.
17. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The thickener for cyanoacrylate adhesives was dissolved in acetone at a concentration of 10% by mass, and the YI value measured using a cuvette having a thickness of 1 cm was 0.1 to 2.
18. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The pH of the supernatant aqueous phase measured at room temperature after the solid content was settled was 2 to 9 when 20 g of the cyanoacrylate adhesive thickener and 100 g of pure water were dispersed by stirring and then left to stand.
19. An adhesive, characterized in that: The adhesive contains the thickener for a cyanoacrylate adhesive according to any one of claims 1 to 18 and an alkyl cyanoacrylate.
20. The adhesive according to claim 19, wherein The viscosity of the adhesive at 25° C. is 0.5-10 Pa·s.
21. The adhesive according to claim 19, wherein The mass ratio of the alkyl cyanoacrylate is 50 mass % or more relative to 100 mass % of the adhesive.
22. The adhesive of claim 19, wherein The alkyl cyanoacrylate is selected from methyl cyanoacrylate, ethyl cyanoacrylate, propyl cyanoacrylate, isopropyl cyanoacrylate, butyl cyanoacrylate, isobutyl cyanoacrylate, octyl cyanoacrylate, methoxyethyl cyanoacrylate, and ethoxyethyl cyanoacrylate.
Citation Information
Patent Citations
JP1976031956B1
Thickening of alpha-cyanoacrylate adhesive
JP1992015267B2
Resin composition, thickener
JP2018178076A
Sterilized cyanoacrylate solutions containing thickeners
CN1378463A
Thickener and method for producing the same
JP2008174574A